2014
DOI: 10.1128/aem.03035-13
|View full text |Cite
|
Sign up to set email alerts
|

Community Dynamics and Activity of Ammonia-Oxidizing Prokaryotes in Intertidal Sediments of the Yangtze Estuary

Abstract: d Diversity, abundance, and activity of ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) were investigated using the ammonia monooxygenase ␣ subunit (amoA) in the intertidal sediments of the Yangtze Estuary. Generally, AOB had a lower diversity of amoA genes than did AOA in this study. Clone library analysis revealed great spatial variations in both AOB and AOA communities along the estuary. The UniFrac distance matrix showed that all the AOB communities and 6 out of 7 AOA communities in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
90
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 67 publications
(120 reference statements)
10
90
0
Order By: Relevance
“…In turn, the AP could favor the microorganism guilds expressed by high PNR and PDR as well as corresponding gene abundances. This is agreement with previous studies, which reported that P could facilitate nitrifiers (Zheng et al, 2014) and denitrifiers (Graham et al, 2010). Phylogenetic analysis indicated AOA in the treatments with iron-rich soil could be clustered into one group with OUT1 as dominant OUT (Fig.…”
Section: Simultaneous Improvement Of P and N Removal And Mechanismssupporting
confidence: 82%
See 1 more Smart Citation
“…In turn, the AP could favor the microorganism guilds expressed by high PNR and PDR as well as corresponding gene abundances. This is agreement with previous studies, which reported that P could facilitate nitrifiers (Zheng et al, 2014) and denitrifiers (Graham et al, 2010). Phylogenetic analysis indicated AOA in the treatments with iron-rich soil could be clustered into one group with OUT1 as dominant OUT (Fig.…”
Section: Simultaneous Improvement Of P and N Removal And Mechanismssupporting
confidence: 82%
“…Noticeably, P could favor nitrifying and denitrifying guilds in many habitats. For instance, in the intertidal sediments of the Yangtze Estuary, TP had a significant correlation with both communities of AOA and AOB (Zheng et al, 2014). Further, in batch experiments with filtrate water from groundwater filters, the nitrification process could be effectively stimulated by adding phosphoric acid (de Vet et al, 2012).…”
Section: Introductionmentioning
confidence: 82%
“…LT2FB (Mintie et al 2003), and N. multiformis (Norton et al 2002) and thus belonged to Nitrosospira cluster three. Several bands (1 through 6, 8 11, C9, and C12) were related with two Nitrosomonadales species from paddy soil and Yangtze Estuary sediments (Wu et al 2011;Zheng et al 2014) and were recognized as Nitrosomonadales-like sequences. Most of the AOB amoA OTUs belongs to cluster three (63 OTUs, 61 %), which the most dominant cluster.…”
Section: Genetic Profiling Of Bacterial and Archaeal Amoa Genesmentioning
confidence: 99%
“…Other nutrient elements such as available phosphorus could affect the community composition of AOA [9,12]. Moreover, the concentration of organic carbon was found to significantly correlate with the community composition of AOA and AOB in the intertidal sediments of the Yangtze Estuary [15]. Moreover, the effects of nutrient levels on the abundance, diversity, and community compositions of AOA and AOB have been investigated.…”
mentioning
confidence: 99%
“…Previous studies have investigated the distribution of AOA and AOB in lake sediments [9][10][11][12][13], the rhizosphere of freshwater macrophytes [14], estuary sediments [15], mangrove sediments [16], and marine sediments [1,17]. It has been found that AOA dominated in marine sediments [1,17], indicated by its better adaptation to anaerobic, low pH, and low ammonia habitats than AOB [18][19], whereas higher nutrients in the freshwater sediments promoted AOB dominance, such as river sediments [20], mangrove sediments [16,21], and shore side wetlands [22].…”
mentioning
confidence: 99%